Faktor -faktor yang Memengaruhi Usahatani Anggur di Desa Wisata Ciganjeng Kabupaten Tasikmalaya - Jakiyah, Ulpah; Umbara, Dona Setia (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Grape farming activities in Pangandaran Regency are an effort to sustain livelihoods on suboptimal land. Grape farming is carried out in every home garden. Grape farming is still done in a simple manner with limited land area. This study aims to analyze the factors that influence grape farming in Pangandaran Regency. This regency has the potential for grape cultivation, but productivity and efficiency still vary among farmers. One example is the grape farmers in Ciganjeng Village, Pangandaran Regency, where 34 farmers are engaged in grape farming. Grape farming activities are managed by the Taruna Tani Mekar Bayu Farmer Group. The farmer group conducts training and provides grape seedlings. The study uses a quantitative approach. The data collected includes land area, number of seedlings, labor, fertilizer use, and production costs. Data analysis was performed using multiple linear regression to determine the effect of each factor on farming activities. The results showed that the variables of land area, number of seedlings, and labor had a significant effect on the income level of grape farmers, while the factors of farming experience and production costs had no significant effect. The coefficient of determination value showed that the model was able to explain most of the variation in farming income. These findings indicate the importance of improving the efficiency of production input use and strengthening farmers' capacity through training and technical assistance. In addition, efforts are needed to improve the productivity and sustainability of grape farming in Pangandaran Regency.